Reintegration of Persons Returning from Labor Migration and Ensuring Their Employment - Ezoza Tursunalieva; Zarnigor Azamova (Periodica Journal, 2022)
Labor migration is a special type of migration at the present stage of development of human society in order to find a decent job and high income, and it has become one of the main means of solving acute problems of employment and wages in underdeveloped countries with complex economies. Of course, Uzbekistan, having achieved political independence, but faced with the need to urgently solve the complex problems of the legacy of the past in socio-economic development, could not stay away from the process of labor migration, a phenomenon of the 20th century. In this article, a study was conducted that the reintegration of persons returning from labor migration, including ensuring their employment, improving their professional skills and encouraging entrepreneurial initiative, is a topical issue today
Keywords: Migration; unemployment; labor migrant; respondents